In vitro Assessment of Bond Strength of three Luting Agents to Fiber Reinforced Composite Posts - Azita Kaviani; Hengameh Alinejad; Fatemeh Dabaghi Tabriz (Majalah-i ̒ilmī pizishkī-i jundī/shapūr, 2013)
Background and Objective:The increasing demand for esthetic posts and cores has led to the development of Metal–free post and core systems. Fiber–reinforced composite posts are one of them. The aim of this study was to evaluate bond strength of three adhesive–resin–cements to fiber posts using push– out test. Subjects and Methods: In this experimental in vitro study. Thirty endodontically treated teeth were randomly divided into three groups (n=10 each). Posts were luted with three resin cements (Rely x ARC, Multi link, Panavia F2). Cemented posts were sectioned in equal thirds using cutting machine. Each slice was polished by a soft and wet abrasive paper in order to get a 2mm thickness. Loading was performed by a testing machineat at a speed of 1mm/min until the post was dislodged. Data were analyzed using post hoc-test and ANOVA tests with P<0.05 as the level of significance.Results: The type of cement bond strength did not vary significantly between coronal and middle sections. However, there were significant differences between apical sections of Rely x ARC and Multi link groups (P=0.032). Conclusion: Bond strength to the fiber post was affected by the type of cement and root regions.